2022
DOI: 10.3389/fimmu.2022.893137
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant HSP90 Expression in Lymphocytes and HSP90 Response to Anti-PD-1 Therapy in Lymphoma Patients

Abstract: HSP90 family of molecular chaperones has been shown to be implicated in various stages of tumor growth and development. Recent studies have highlighted the role of extracellular HSP90 in tumor immunology, however, the role that HSP90 plays in the regulation of immune responses and the impact of cancer immunotherapy, including immune checkpoint blockade, on HSP90 is still unclear. Here we assessed the surface and intracellular expression of constitutive cytosolic HSP90β isoform, mitochondrial HSP90 homolog TRAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…HSPs play important roles in folding, degradation, and maturation of client proteins [ 5 , 6 ]. Dysregulated expression of various HSP members has been reported in various tumors, where high HSP expression is typically associated with an unfavorable clinical outcome [ 14 , 40 , 42 , 43 , 44 ]. Several studies have shown that HSP90 inhibitors downregulate surface PD-L1 expression and may also potentiate the effect of PD-1 and CTLA-4 treatments [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HSPs play important roles in folding, degradation, and maturation of client proteins [ 5 , 6 ]. Dysregulated expression of various HSP members has been reported in various tumors, where high HSP expression is typically associated with an unfavorable clinical outcome [ 14 , 40 , 42 , 43 , 44 ]. Several studies have shown that HSP90 inhibitors downregulate surface PD-L1 expression and may also potentiate the effect of PD-1 and CTLA-4 treatments [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that HSP90 inhibitors downregulate surface PD-L1 expression and may also potentiate the effect of PD-1 and CTLA-4 treatments [ 39 ]. In our previous study, we found that the PD-1 inhibitor (Nivolumab) affects HSP90 expression in peripheral blood and bone marrow lymphocytes in refractory or recurrent Hodgkin’s lymphoma patients [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsp90 inhibitors. Heat shock protein 90 (Hsp90) is an oncogene that promotes c-MYC mRNA stability (108), regulates tumour immunology (109) and participates in aberrant metabolism of lymphoma cells (110). Hsp90 inhibitors act as novel senolytic agents (111) that have rapidly developed in preclinical research on lymphomas.…”
Section: Treatment Strategies For Senescence-mediated Lymphoma Resist...mentioning
confidence: 99%